2022
DOI: 10.1021/acs.jpcb.1c09092
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry Dissolved in Ionic Liquids. A Theoretical Perspective

Abstract: The theoretical treatment of ionic liquids must focus now on more realistic models while at the same time keeping an accurate methodology when following recent ionic liquids research trends or allowing predictability to come to the foreground. In this Perspective, we summarize in three cases of advanced ionic liquid research what methodological progress has been made and point out difficulties that need to be overcome. As particular examples to discuss we choose reactions, chirality, and radicals in ionic liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…4 Key features of ionic liquids, in this regard, relate to the high thermal and chemical stability and the weakly coordinating properties. 1,5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Key features of ionic liquids, in this regard, relate to the high thermal and chemical stability and the weakly coordinating properties. 1,5…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the synthesis of metastable compounds in ionic liquids was mainly focused on metal halides, metal selenides/tellurides or metal clusters. 1–5 The synthesis of new metal oxides and compounds using metal oxides as starting materials, in contrast, was barely addressed, which can be attributed to the high lattice energy of many metal oxides and their low solubility in ionic liquids. Several studies, however, have successfully shown options to dissolve metal oxides in ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“… Delocalization of charge over several atoms and asymmetry in either the size or shape of the cation or anion are essential in the construction of these materials. The physical and chemical properties of ILs are fundamentally related to their solvent structure. , Due to their extensive potential to alter physical and chemical behavior through functionalization, considerable effort has been put forth by the IL community to better understand the nature of these intermolecular interactions. …”
Section: Introductionmentioning
confidence: 99%
“…In spite of these efforts, realistic applications from sustainable chemistry often require complex or involved models of the underlying chemistry and large computing time. Examples are the inclusion of liquids or solvents, for example ionic liquids, [11][12][13][14] but also the appropriate description of interfaces 15,16 or systems from energy devices. [17][18][19] When using such approximate methods, the assessment of the errors included is of high importance.…”
Section: Introductionmentioning
confidence: 99%